Effect of Vitamin D Supplementation, Omega-3 Fatty Acid Supplementation, or a Strength-Training Exercise Program on Clinical Outcomes in Older Adults - Heike A. Bischoff‐Ferrari; Bruno Vellas; René Rizzoli; Reto W. Kressig; José António Pereira da Silva; Michael Blauth; David T. Felson; E. V. McCloskey; Bernhard Watzl; Lorenz C. Hofbauer; Dieter Felsenberg; Walter C. Willett; et al. (2020)
The benefits of vitamin D, omega-3 fatty acids, and exercise in disease prevention remain unclear.To test whether vitamin D, omega-3s, and a strength-training exercise program, alone or in combination, improved 6 health outcomes among older adults.Double-blind, placebo-controlled, 2 × 2 × 2 factorial randomized clinical trial among 2157 adults aged 70 years or older who had no major health events in the 5 years prior to enrollment and had sufficient mobility and good cognitive status. Patients were recruited between December 2012 and November 2014, and final follow-up was in November 2017.Participants were randomized to 3 years of intervention in 1 of the following 8 groups: 2000 IU/d of vitamin D3, 1 g/d of omega-3s, and a strength-training exercise program (n = 264); vitamin D3 and omega-3s (n = 265); vitamin D3 and exercise (n = 275); vitamin D3 alone (n = 272); omega-3s and exercise (n = 275); omega-3s alone (n = 269); exercise alone (n = 267); or placebo (n = 270).The 6 primary outcomes were change in systolic and diastolic blood pressure (BP), Short Physical Performance Battery (SPPB), Montreal Cognitive Assessment (MoCA), and incidence rates (IRs) of nonvertebral fractures and infections over 3 years. Based on multiple comparisons of 6 primary end points, 99% confidence intervals are presented and P < .01 was required for statistical significance.Among 2157 randomized participants (mean age, 74.9 years; 61.7% women), 1900 (88%) completed the study. Median follow-up was 2.99 years. Overall, there were no statistically significant benefits of any intervention individually or in combination for the 6 end points at 3 years. For instance, the differences in mean change in systolic BP with vitamin D vs no vitamin D and with omega-3s vs no omega-3s were both -0.8 (99% CI, -2.1 to 0.5) mm Hg, with P < .13 and P < .11, respectively; the difference in mean change in diastolic BP with omega-3s vs no omega-3s was -0.5 (99% CI, -1.2 to 0.2) mm Hg; P = .06); and the difference in mean change in IR of infections with omega-3s vs no omega-3s was -0.13 (99% CI, -0.23 to -0.03), with an IR ratio of 0.89 (99% CI, 0.78-1.01; P = .02). No effects were found on the outcomes of SPPB, MoCA, and incidence of nonvertebral fractures). A total of 25 deaths were reported, with similar numbers in all treatment groups.Among adults without major comorbidities aged 70 years or older, treatment with vitamin D3, omega-3s, or a strength-training exercise program did not result in statistically significant differences in improvement in systolic or diastolic blood pressure, nonvertebral fractures, physical performance, infection rates, or cognitive function. These findings do not support the effectiveness of these 3 interventions for these clinical outcomes.ClinicalTrials.gov Identifier: NCT01745263.